Novel Referencing Style Based on DOI® for Digital Publications - KK, Mueen Ahmed; Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
The various formats of referencing styles adopted by different scholarly disciplines often leads to confusions, errors and lack of traceability of resources cited. To address these challenges we herewith propose a simple and easy to use referencing style based on the digital object identifier (the DOI® system), which in our opinion will not only improve the traceability of resources cited but will also lead to harmonisation of referencing across various scholarly disciplines. With increasing adoption of digital publications, it is our view that that the novel DOI® based referencing system proposed here will be resourceful and less prone to potential citation errors.
Keywords: Citations; Referencing; Scholarly work; Manuscripts; Styles